تقلص الراتنجات السنية السيالة - معروف, علي (Latakia University Journal -Medical Sciences Series, 2019)
أجري هذا البحث بهدف تقييم مدى ثبات أبعاد مجموعة من المواد الحاشية التجميلية الضوئية السيالة ذات تراكيب كيميائية مختلفة. أجريت الدراسة باستخدام طريقة العينة الملصقة على أربع مواد من الراتنج المركب السني المتصلب ضوئياً وهيTetric Evo Flow (T) Dyract Flow (DY), Admira Flow (AF) Revolution Formula2(R). حيث تم تصليب كل عينة على حدة لمدة أربعين ثانية, وبشدة ضوئية تعادل 750 مللي وات/ سم2, وكررت التجربة لكل عينة ثلاث مرات, ومدة كل تجربة 30دقيقة وحللت النتائج باستخدام(One Way Anova) وكذلك طريقة الـ (Scheffé and Student- Newman- Kelus ) بنسبة خطأ (0.05 =P ) للتحقق من القيم المتجانسة: -1 أظهرت النتائج وجود اختلافات جوهرية بين المواد المدروسة, كما أن إنقاص نسبة المسحوق في المركبات التي تحوي (Bis– GMA , TEGDMA ) يزيد من عملية الانكماش. -2 أظهرت مادة الأورموسير(AF) أقل قيمة من قيم الانكماش التماثري في درجة حرارة الغرفة العادية. -3 أظهرت مادة الكومبومير (DY ) أكبر قيمة انكماش تماثري وبعدها مادة الدايميثياكريليت (R ). -4 أظهرت مواد الميتاكريلات الـ (R و T) قيماً متوسطة بين الأرموسير و الكومبومير. -5تزداد قيمة الانكماش التماثري بازدياد درجة الحرارة من 23 إلى 37. (P<0.05) This research was conducted to assess the stability of the dimensions of different chemical structures of light-cured cosmetic dental materials. Determination setting shrinkage – strain data were obtained by Bonded – Disk method.Four light cured composite materials were examined: Admira Flow (AF), Dyract Flow (DY),TetricEvoFlow (T),Revolution Formula2 (R). The materials were cured separately for 40 seconds using light unit with an intensity of 750 mw / cm2. Setting shrinkage – strain data (N: 3) were obtained at two different temperatures: 23Cْ and 37Cْ. The results showed that: The Ormocer material (AF) exhibited the lowest mean of shrinkage strain. The Compomer material (DY) exhibited the highest mean of shrinkage strain, followed by The Dimethacrylate composite (R). The Dimethacrylate composite (T, R) exhibited medium values between the Ormocer and Compomer material. All restorative materials studied exhibited significant differences in shrinkage-strain due to the increase in temperature from 23 to 37 Cْ.